Śrī Rāmakrshṇapatnī Śrī Śāradādevī : jīvanakathā - Khānolakara, Gaṅgādhara Devarāva (SAMP early 20th-century Indian books project, 1953)
Biography of Sarada Devi, 1853-1920, wife of Ramakrishna, 1836-1886, Hindu religious leader.